Telling God's story: Bible, church, and narrative theology - Loughlin, Gerard (Cambridge University Press, 1996)
This book presents narrative theology as radically orthodox. It is orthodox because it is in the tradition of all those who maintain the priority of the story of Jesus, as it is sacramentally performed in the Church; and radical because it eschews all modern attempts to found Christian faith on some other story, such as that of reason, critical history or human consciousness. Acknowledging the indeterminacy and textuality of human existence, Telling God's Story presents the Christian life as a truly postmodern venture: the groundless enactment of God's 'future now'. In the epilogue this book focuses on the Eucharist as the sacramental site in which the story and body of Christ consumes and is consumed. Through this bodily telling and consumption the Church is enabled to receive again God's gift of return and to be the telling of God's story, once more.